Dental porcelain
A dental porcelain with controlled TiO2 and aluminosilicate glass composition addresses the issue of metal color visibility and thermal mismatch in zirconia crowns, providing effective shielding and crack resistance.
Patent Information
- Application Number
- JP2021076884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-04-28
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2041-04-28
AI Technical Summary
Existing dental porcelains fail to adequately shield underlying metal color in zirconia crowns, leading to discoloration and cracks due to mismatched thermal expansion coefficients, especially when used with implants or abutments.
A dental porcelain composition containing specific amounts of crystalline and amorphous TiO2, combined with aluminosilicate glass, to achieve high shielding properties, suppress discoloration, and match the thermal expansion of zirconia crowns.
The composition effectively blocks metal color transmission through zirconia crowns while maintaining high whiteness and preventing thermal cracking, ensuring excellent aesthetic outcomes.
Smart Images

Figure 0007606405000001 
Figure 0007606405000002
Abstract
Description
[Technical field]
[0001] The present invention relates to dental porcelain. [Background technology]
[0002] Since metal fused porcelain needs to mask the metallic color of the base, opaque porcelain has been available in the product lineup for some time, and it has been possible to manufacture highly aesthetic prostheses in which the metallic color is not visible on the surface of the crown. On the other hand, the opaque zirconia prostheses that have been used traditionally can mask the metallic color of the base in cases where implants or abutments are used, even without a product with strong masking properties such as opaque porcelain, and it has been possible to manufacture highly aesthetic prostheses.
[0003] In recent years, with the widespread use of high-strength and highly transparent zirconia-based products, there has been a problem in that the color of the underlying metal cannot be sufficiently shielded when an implant or abutment is used. Therefore, there is a demand for opaque porcelain materials with high shielding properties, even in porcelain materials for fusing to zirconia. Furthermore, while conventional colored porcelain powders tend to provide better shielding than white porcelain, users who prefer bleached colors tend not to like colored prostheses. The highly white bleached colors required for zirconia prostheses often do not provide strong shielding, and in cases where implants or abutments are used, the underlying metal color is likely to show on the crown surface, making it difficult to produce highly aesthetic prostheses.
[0004] Patent Document 1 describes a material that is resistant to discoloration after baking to metal, has a high metal color shielding power, and has a thermal expansion coefficient of 10.0 to 13.0 × 10 in the temperature range of 25 to 450 °C. -6 / °C. In Patent Document 1, the dental opaque porcelain contains CeO 2 15 to 50% by weight of aluminosilicate glass (SiO 2 It is disclosed that the composition contains 40 to 50% by weight of the above ingredient: 50 to 60% by weight).
[0005] Patent Document 2 describes a porcelain composition for use as an opaque body on a dental alloy. In Patent Document 2, the porcelain composition has a thermal expansion coefficient of about 15.5 to about 17×10, which is almost equal to the thermal expansion coefficient of the alloy, in the temperature range of 25 to 500° C. -6 / °C, and aluminosilicate glass with about 80-90% by weight (Na 2 Patent Document 2 also discloses a composition containing about 4 to about 6% by weight of an O component and about 10 to about 20% by weight of an opacifying agent. 2 O 3 , ZnO, TiO 2 , ZrO 2 , ZrSiO 4 , CEO 2 , Ta 2 O 5 , SnO 2 and mixtures thereof are disclosed.
[0006] Patent Document 3 describes an alkali silicate glass (B 2 O 3 The alkali silicate glass has a low thermal expansion coefficient of 5.5 to 12.5×10 which can be used for ceramics or glass ceramics. -6 It is disclosed that the glass has a thermal expansion coefficient of 100 / °C, and has high translucency and does not crystallize when heated in a temperature range of 600 to 1000°C. Preferable components of the alkali silicate glass are CaO, F, P 2 O 5 , Li 2 O, BaO, ZnO, CeO 2 In addition to the addition of TiO 2 +ZrO 2 Composite components (0.2 to 5.0% by weight) are listed. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 10-94550 [Patent Document 2] JP 2003-503431 A [Patent Document 3] Japanese Patent Application Publication No. 11-21145 Summary of the Invention [Problem to be solved by the invention]
[0008] However, although the dental opaque porcelain of Patent Document 1 has high shielding properties and is less likely to discolor after being baked onto metal, it contains TiO 2 When using this as a shielding material, as shown in Comparative Example 2 of Patent Document 1, firing at a temperature of 900°C to 1000°C causes the porcelain to turn yellow, affecting the color tone. In addition, the opaque porcelain of Patent Document 2 has a problem that the thermal expansion coefficient is too high for zirconia, causing cracks in the porcelain during firing. Furthermore, the glass of Patent Document 3 has a thermal expansion coefficient suitable for zirconia, but has a high translucency, so there is a problem that it cannot shield the metallic color of the base that shows through the zirconia crown. Therefore, a dental porcelain that shields the metallic color, suppresses discoloration of the porcelain, and has a thermal expansion coefficient suitable for zirconia crowns has not been obtained.
[0009] The problem to be solved by the present invention is to provide a dental porcelain material that has high shielding properties, inhibits discoloration of the porcelain material, and is suitable for zirconia crowns. [Means for solving the problem]
[0010] As a result of intensive research to solve the above problems, the present inventors have discovered a crystalline TiO 2 The inventors have found that the above-mentioned problems can be solved by controlling the amount of and have carried out further research based on this finding, which has led to the completion of the present invention.
[0011] That is, the present invention includes the following inventions. [1] Glass components and crystalline TiO 2 The crystalline TiO2 The dental porcelain material has a content of 15% by mass or more and 25% by mass or less. [2] The glass component is amorphous TiO 2 The crystalline TiO 2 and the amorphous TiO 2 The dental porcelain according to [1], wherein the total mass of the above is 18 mass% or more and 35 mass% or less. [3] The amorphous TiO 2 The content of said crystalline TiO 2 The dental porcelain according to [2], wherein the content of said porcelain is less than or equal to 1. [4] The glass component contains an aluminosilicate glass and amorphous TiO 2 When the total amount of the aluminosilicate glass excluding the above is taken as 100 mass%, the aluminosilicate glass contains 60.0 mass% to 70.0 mass% of SiO 2 The dental porcelain material according to any one of [1] to [3], [5] The aluminosilicate glass is made of amorphous TiO 2 When the total amount excluding is 100 mass%, express it as mass%. Al 2 O 3 8.0%~12.0% CaO 0.5%~4.0% K 2 O 7.0%~10.0% Na 2 O 6.0%~9.0% The dental porcelain according to [4], further comprising: [6] The glass component contains an aluminosilicate glass and amorphous TiO 2 When the total amount of the aluminosilicate glass excluding 2 O and K 2 The dental porcelain according to any one of [1] to [4], wherein the total content together with O is 12.0 mass % to 20.0 mass %. [7] The crystalline TiO 2 The dental porcelain according to any one of [4] to [6], wherein a mass ratio of the content of said component (a) to the content of said aluminosilicate glass is 25:65 to 15:80. [8] The thermal expansion coefficient at 30℃~450℃ is 8.0×10 -6 / ℃ or more 10.0×10 -6 / °C or less. [9] The dental porcelain material according to any one of [1] to [8], which has a transmittance of 8% or less after firing at 880°C to 980°C.
[10] The dental porcelain according to any one of [1] to [9], wherein, in color measurement data according to the L*a*b* color system after firing at 880°C to 980°C, L* is 90.0 or more.
[11] The main component of the crystalline component is the crystalline TiO 2 The dental porcelain material according to any one of [1] to
[10] ,
[12] Glass components and crystalline TiO 2 The method for producing a dental porcelain according to any one of [1] to
[11] , comprising a step of heat treating the above at 750°C to 880°C.
[13] A method for producing a dental prosthesis, comprising the steps of applying the dental porcelain according to any one of [1] to
[11] onto a zirconia base material, and firing the dental porcelain at 880°C to 980°C. Effect of the Invention
[0012] According to the present invention, a dental porcelain material having high shielding properties, suppressing discoloration of the porcelain material, and suitable for a zirconia crown can be provided. According to the present invention, when a highly translucent zirconia crown using a dental porcelain material is placed on a metal such as an implant or a titanium abutment, the metal color showing through the zirconia crown can be shielded, discoloration can be suppressed, and the high whiteness required for a zirconia prosthesis can be maintained, making it possible to produce a prosthesis with excellent aesthetics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Crystalline TiO in dental porcelain 2 Content of The dental porcelain of the present invention is a glass component and a crystalline TiO 2 The crystalline TiO 2The content of crystalline TiO is 15% by mass or more and 25% by mass or less. 2 The content of TiO is preferably 17% by mass or more and 23% by mass or less, and more preferably 19% by mass or more and 21% by mass or less. This makes it possible to mask the metallic color showing through the zirconia crown. In addition, crystalline TiO 2 Since the crystalline TiO is contained in the above amount, in a case where a highly translucent zirconia crown using dental porcelain is placed on a metal such as an implant or a titanium abutment, the zirconia crown does not discolor and maintains a high degree of whiteness, so that the aesthetics of the zirconia crown can be maintained. 2 If the content is less than 15% by mass, the shielding properties are reduced, and if it is 25% by mass or more, it will not be possible to sinter at the appropriate sintering temperature, and the shielding properties will also be reduced. 2 The content of TiO 2 The amount of and the conditions of the heat treatment described below can be adjusted to the desired range.
[0014] In addition, the dental porcelain of the present invention is a crystalline TiO 2 In addition, amorphous TiO 2 The dental porcelain of the present invention may contain amorphous TiO 2 When it contains TiO 2 The total mass of the crystalline and amorphous portions is preferably from 18% by mass to 35% by mass, more preferably from 19% by mass to 32% by mass, and even more preferably from 20% by mass to 30% by mass, in order to provide better shielding properties and to easily maintain high whiteness.
[0015] In addition, the dental porcelain of the present invention is amorphous TiO 2 When it contains, amorphous TiO 2 The content of is preferably 10% by mass or less, more preferably 9% by mass or less, and even more preferably 8% by mass or less, based on the total amount of the dental porcelain. 2 When it contains, amorphous TiO 2 The content of crystalline TiO is based on mass. 2It is preferable that the dental porcelain of the present invention has an amorphous TiO 2 In the case of containing TiO, it is preferable to use amorphous TiO, because it has better shielding properties, is easier to maintain high whiteness, and is easier to obtain a thermal expansion coefficient suitable for zirconia. 2 The content of TiO and crystalline TiO 2 The mass ratio of the content of amorphous TiO 2 : crystalline TiO 2 = 1:2 to 1:8 is preferable, 1:2.5 to 1:7 is more preferable, and 1:3 to 1:6 is even more preferable. 2 " refers to TiO that exists as a crystalline substance. 2 and TiO that exists as amorphous in the glass. 2 This means both.
[0016] In the dental porcelain of the present invention, the main component of the crystalline component is crystalline TiO 2 In this specification, the term "main component" refers to the component that is contained in the largest amount. 2 The content is preferably 50% by mass or more.
[0017] [Glass components] Dental porcelain consists of glass components and crystalline TiO 2 wherein the glass component is SiO 2 It is preferable that the glass component contains an aluminosilicate glass containing SiO 2 , Al 2 O 3 , CaO, K 2 O and Na 2 It is more preferable that the glass component contains an aluminosilicate glass containing O as an essential component. The content of the aluminosilicate glass in the glass component is preferably 60% by mass or more, more preferably 70% by mass or more. When the glass component contains the above-mentioned components, it can have both chemical stability and various physical properties as a dental porcelain material. In this specification, the percentage of the content of each component in the glass means mass %. In addition, hereinafter, the content of each component is expressed as the percentage of amorphous TiO 2The total amount of the aluminosilicate glass excluding the above is expressed as 100 mass %.
[0018] [SiO 2 Content] In the aluminosilicate glass, SiO 2 The content of SiO is preferably 60.0% to 70.0%, more preferably 60.5% to 69.5%, further preferably 61.5% to 68.5%, and particularly preferably 63.0% to 67.0%. 2 Within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0019] [Al 2 O 3 Content] In the aluminosilicate glass, Al 2 O 3 The content of Al is preferably 8.0% to 12.0%, more preferably 8.5% to 10.0%, further preferably 8.7% to 9.8%, and particularly preferably 8.9% to 9.6%. 2 O 3 When the content of is within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0020] [CaO content] In the aluminosilicate glass, the CaO content is preferably 0.5% to 4.0%, more preferably 1.5% to 2.5%, further preferably 2.0% to 2.4%, and particularly preferably 2.1% to 2.4%. When the CaO content is within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0021] [K 2 O content] In the aluminosilicate glass, K 2 The content of O is preferably 7.0% to 10.0%, more preferably 8.5% to 9.9%, further preferably 8.7% to 9.7%, and particularly preferably 8.9% to 9.5%. 2 When the content of O is within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0022] [Na 2 O content] In the aluminosilicate glass, Na 2 The O content is preferably 6.0% to 9.0%, more preferably 7.5% to 8.6%, further preferably 7.7% to 8.4%, and particularly preferably 7.9% to 8.2%. 2 When the content of O is within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0023] The glass component includes an aluminosilicate glass, and the amorphous TiO 2 When the total amount of the aluminosilicate glass excluding 2 O and K 2 The total content with O is preferably 12.0 mass% to 20.0 mass%, more preferably 12.5 mass% to 19.5 mass%, further preferably 13.0 mass% to 19.0 mass%, and particularly preferably 13.5 mass% to 18.5 mass%. 2 O and K 2 When the total content of TiO and O is within the above range, the balance with other components is excellent, and TiO 2 The amorphization of TiO is suppressed, and crystalline TiO 2 It is easy to maintain a predetermined amount in the dental porcelain.
[0024] [Other glass components (optional components)] The aluminosilicate glass further comprises Li 2 O, MgO, ZrO 2 It can contain optional components such as Li 2 The content of O is, for example, 0% to 2.0%, and may be 0.05% to 1.4%. The content of MgO is, for example, 0% to 3.0%, and may be 0.05% to 2.0%, or may be 0.1% to 1.0%. 2 The content of is, for example, 0% to 12.0%, and may be 0% to 10%, 0% to 5%, or even 0.1% to 4%. The aluminosilicate glass may contain a trace component that promotes melting, homogenization, clarification, etc. of the glass. The trace component may be, for example, Sb 2 O 3 , CEO 2 , SnO 2 , Fe 2 O 3 , P 2 O 5 At least one selected from the group consisting of Sb, Cl and F. 2 O 3 The content of oxides that can have multiple valences among the trace components is calculated by converting the content into the valence of the trace component exemplified above. Therefore, for example, FeO is 1 / 2Fe 2 O 3 It is calculated by converting it into Sb 2 O 3 The total content of the trace components listed from to F may be 0% to 3.0%, preferably 0.1% to 2.0%, and more preferably 0.3% to 1.5%. Optional components other than those mentioned above that the aluminosilicate glass may contain include B, 2 O 3 , SrO, BaO, and ZnO. However, the aluminosilicate glass is preferably B 2 O 3 The aluminosilicate glass may contain up to 2.0%, or even up to 1.0%, of each of the components listed below. 2 O3 In the present specification, "substantially free" means that the content is less than 0.5% by mass, further less than 0.1% by mass, and particularly less than 0.01% by mass.
[0025] In addition, Sb 2 O 3 and CEO 2 As long as the above-mentioned components such as TiO are included as amorphous, the components are referred to herein as TiO 2 Except when the above, the total amount of the component is calculated by including it in the components of the aluminosilicate glass.
[0026] The dental porcelain of the present invention is a crystalline TiO 2 The mass ratio of the content of the aluminosilicate glass to the content of the aluminosilicate glass is preferably 25:65 to 15:80, and from the viewpoints of achieving better shielding properties, easier maintenance of high whiteness, and easier acquisition of a thermal expansion coefficient more suitable for zirconia, is more preferably 21:75 to 16:80, and further preferably 19:73 to 18:75.
[0027] [Additives other than glass components in dental porcelain] The dental porcelain may further contain, in addition to the glass component, a pigment, a fluorescent agent, a shielding material (opacifying agent), etc. As the pigment or fluorescent agent, for example, an oxide of at least one element selected from the group consisting of P, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er may be used. As the shielding material, for example, ZrO 2 , ZrSiO 4 , SnO 2 and CeO 2 At least one crystalline compound selected from the group consisting of the pigment, the fluorescent agent, and the shielding agent may be one compound or multiple compounds. In one embodiment, crystalline CeO 2 The dental porcelain is substantially free of
[0028] [Compositional analysis of glass components in dental porcelain] In dental porcelain, SiO 2 Ingredients, Al 2 O 3 component, CaO component, K 2 O components and Na 2 The content of the O component can be measured, for example, by fluorescent X-ray analysis. 2 The content of the O component can be measured, for example, by atomic absorption spectrometry. 2 O 3 The content of the component and the ZnO component can be measured, for example, by inductively coupled plasma (ICP) emission spectrometry. Alternatively, the composition of the dental porcelain can be calculated from the blending ratio of each component in the raw materials constituting the glass ceramic composition, which is the powder of the dental porcelain, and the glass ceramic sintered body obtained by firing the dental porcelain.
[0029] Next, an example of a method for producing dental porcelain will be described.
[0030] [Preparation of glass raw materials] First, the raw glass of the ceramic material is prepared. For example, raw materials (oxides, carbonates, etc.) corresponding to the above-mentioned oxide compositions are prepared and mixed. Next, the mixed raw materials are melted in a crucible at 1300°C to 1600°C for 2 to 8 hours, and then the melt is quenched in water to prepare cullet. The glass cullet is then crushed in a ball mill or pot mill and sieved to obtain a predetermined particle size range.
[0031] [Preparation of dental porcelain] Next, the prepared primary glass powder (glass component) and TiO 2 The mixed powder is heat-treated at 750°C to 880°C for 0.5 to 2 hours. The heat treatment temperature is preferably 770°C to 850°C, more preferably 790°C to 820°C. If the heat treatment temperature is too high, TiO 2 is dissolved in the glass more than necessary, forming crystalline TiO 2 If the heat treatment temperature is too low, the content of TiO 2 does not fuse with glass, and crystalline TiO2 This causes problems when mixing with the special liquid to create a product. 2 The fused fired product is crushed, and the crushed product is further crushed in a pot mill until it has a particle size within a predetermined range. The crushed product is then sieved to remove the coarse particles, thereby obtaining a ceramic powder.
[0032] [Firing temperature of dental porcelain] In addition, a preferred embodiment of the present invention includes a method for producing a dental prosthesis, comprising the steps of applying the dental porcelain onto a zirconia substrate and firing the dental porcelain at 880° C. to 980° C. The firing temperature of the dental porcelain is preferably 880° C. to 980° C., more preferably 900° C. to 960° C., and even more preferably 920° C. to 940° C. This makes it possible to suppress damage to the zirconia crown, for example, when the porcelain is sintered on the zirconia crown. Also, deformation due to overheating can be suppressed.
[0033] [Thermal expansion coefficient of dental porcelain] The thermal expansion coefficient of dental porcelain at 30℃ to 450℃ is 8.0×10 -6 / ℃ or more 10.0×10 -6 / ℃, preferably less than 8.5×10 -6 / ℃ or more 9.5×10 -6 / °C or less is more preferable. This makes it possible to suppress the occurrence of defects such as cracks even when a zirconia crown is used as a base material and heated. The method for measuring the thermal expansion coefficient of the dental porcelain is as described in the Examples below.
[0034] [Shielding properties (transmittance) of dental porcelain] The transmittance of the dental porcelain after firing at 880° C. to 980° C. is preferably 8% or less, more preferably 7% or less, and even more preferably 5% or less. This makes it possible to block out metallic colors. The method for measuring the transmittance of the dental porcelain is as described in the Examples below.
[0035] [Discoloration of dental porcelain (whiteness)] The degree of discoloration of the dental porcelain can be measured using a spectrophotometer after firing. In color measurement data according to the L*a*b* color system after firing the dental porcelain at 880°C to 980°C, the L* value is preferably 90.0 or more, more preferably 92.0 or more, and even more preferably 94.0 or more. This makes it possible to manufacture a prosthesis while maintaining the aesthetics of the zirconia crown. The method for measuring the degree of discoloration (whiteness) of the dental porcelain is as described in the Examples below. EXAMPLES
[0036] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples, and many modifications within the technical concept of the present invention are possible by those skilled in the art.
[0037] [Preparation of raw glass] When preparing the primary glass powder, the raw materials (silica, alumina, calcium carbonate, sodium carbonate, potassium carbonate, basic magnesium carbonate, lithium carbonate, etc.) were mixed so as to obtain the composition shown in Table 1. The mixed raw materials were melted in a crucible at 1450°C for 4 hours. The melt was quenched in water to prepare glass cullet, which was then crushed in a ball mill and sieved through a stainless steel #100 mesh sieve to obtain the primary glass powder.
[0038] [Table 1]
[0039] [Preparation of porcelain powder] Prepared primary glass powder and TiO 2 were mixed in the ratios shown in Table 2. The mixed powder was heat-treated at 800 °C for 2 hours. Then, the glass and TiO 2The fused fired product was crushed using a jaw crusher, and the crushed product was further crushed using a ball mill until the average particle size became 15 μm. After that, the crushed product was sieved through a stainless steel #100 mesh sieve to remove coarse particles, and a ceramic powder was obtained. The average particle size can be determined by a laser diffraction scattering method. Specifically, the laser diffraction scattering method can be performed by using a laser diffraction particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) to measure the average particle size on a volume basis using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.
[0040] [Crystalline TiO 2 Measurement of the content of Crystalline TiO contained in porcelain powder 2 The quantitative analysis of TiO was carried out using an X-ray diffraction apparatus. 2 This was carried out by measuring the peak intensity of the crystals. The X-ray diffraction apparatus used was Smart Lab (manufactured by Rigaku Corporation). X-rays were measured using CuKα in the range of 2θ = 23° to 28°, and TiO 2 The area intensity including the first peak intensity of was read. 2 Standard samples with known TiO contents (5, 10, 15, 20, 25, 30 mass%) were prepared, and the area intensity of X-rays from the standard samples was measured to determine the crystalline TiO 2 By creating a correlation equation (approximation) between the content and area intensity, crystalline TiO 2 In the case of glass 1, the crystalline TiO 2 When the content of TiO is X and the area intensity is Y, a calibration curve of Y = 1.28X + 5.23 was obtained. 2 From the area intensity, crystalline TiO 2 becomes quantifiable.
[0041] [Amorphous TiO 2 Measurement of the content of TiO 2The total amount of crystalline and amorphous matter was quantified by elemental analysis using X-ray fluorescence analysis (Rigaku ZSX Primus II). 2 The content of crystalline and amorphous TiO was determined by elemental analysis. 2 Calculate the total amount of crystalline TiO 2 The content was calculated by subtracting
[0042] [Transmittance measurement of dental porcelain] The ceramic powder was molded into pellets and fired at 930℃ for 1 minute. Both sides of the test pieces were polished with #1000 waterproof abrasive paper (C947H, manufactured by Noritake Coated Abrasives Co., Ltd.) to prepare measurement samples with a diameter of 11 mm and a thickness of 0.30 mm. The measurements were performed using a transmission densitometer X-Rite 361T(V) (manufactured by Sakata Inx Engineering Co., Ltd.) to measure the transmission density by applying light with a wavelength of 555 nm. The measured transmission density value was entered into the following formula (1) to calculate the transmittance. Transmittance [%]=10 -透過濃度 ×100 (1)
[0043] [Measurement of thermal expansion coefficient of dental porcelain] The thermal expansion coefficient was measured in accordance with JIS T 6526 (2012). The test specimens used for the measurements were prepared by forming the ceramic powder into a rod shape (diameter: about 5 mm), firing it at 930°C for 1 minute, and polishing the top and bottom surfaces with waterproof abrasive paper (C947H, Noritake Coated Abrasives Co., Ltd.) with a grit size of #1000 on both sides to a length of 20 mm. The thermal expansion coefficient was measured in the temperature range of 30°C to 450°C at a heating rate of 5°C / min using a thermomechanical analyzer TMA8310 (Rigaku Co., Ltd.).
[0044] [Evaluation of discoloration (whiteness) of dental porcelain] The ceramic powder was molded into a pellet shape, and the test piece was fired at 930°C for 1 minute. Both sides of the test piece were polished with #1000 waterproof abrasive paper (C947H, manufactured by Noritake Coated Abrasives Co., Ltd.) to a diameter of 14 mm and a thickness of 1.20 mm. The test piece was measured using a spectrophotometer CM-3610A (manufactured by Konica Minolta, Inc.) with a D65 light source, measurement mode SCI, measurement diameter / illumination diameter = φ8 mm / φ11 mm, and a white background, and the L* value of the lightness (color space) in the L*a*b* color system (JIS Z 8781-4:2013 Colorimetry-Part 4: CIE 1976 L*a*b* color space) was read. In order to suppress discoloration during firing, it is preferable that L* is 90.0 or more.
[0045] [Table 2]
[0046] In Examples 1 to 5, dental porcelains having high shielding properties and a thermal expansion coefficient suitable for zirconia crowns that do not discolor during firing were obtained. On the other hand, in Comparative Examples 1 to 4, TiO 2 If the amount of is too little or too much, good shielding properties cannot be obtained, and the glass discolors during firing due to differences in the composition of the glass components.
[0047] Unless otherwise stated with respect to numerical ranges set forth herein, any numerical value or range falling within the range should be construed as being specifically set forth herein. [Industrial Applicability]
[0048] The dental porcelain of the present invention can be used for dental prostheses and the like.
Claims
1. Glass components and crystalline TiO 2 The crystalline TiO 2 The content is 15% by mass or more and 25% by mass or less, The glass component contains an aluminosilicate glass, and when the total amount of the aluminosilicate glass excluding amorphous TiO 2 is taken as 100 mass %, the aluminosilicate glass has a content, expressed in mass %, of: SiO 2 60.0-70.0% Al 2 O 3 8.0% to 12.0% CaO 0.5%~4.0% K 2 O 7.0% to 10.0% Na 2 O 6.0% to 9.0% Contains The dental porcelain, wherein the total content of Na 2 O and K 2 O contained in the aluminosilicate glass is 12.0% by mass to 20.0% by mass.
2. The glass component is amorphous TiO 2 The crystalline TiO 2 and the amorphous TiO 2 The dental porcelain according to claim 1, wherein the total mass of the above is 18 mass % or more and 35 mass % or less.
3. The amorphous TiO 2 The content of the crystalline TiO 2 The dental porcelain according to claim 2, wherein the content of
4. The crystalline TiO 2 The dental porcelain according to any one of claims 1 to 3, wherein a mass ratio of the content of said component (I) to the content of said aluminosilicate glass is from 25:65 to 15:
80.
5. Thermal expansion coefficient at 30°C to 450°C is 8.0 x 10 -6 / ℃ or more 10.0 x 10 -6 The dental porcelain according to any one of claims 1 to 4, wherein the temperature is less than 100°C.
6. 6. The dental porcelain according to claim 1, which has a transmittance of 8% or less after firing at 880°C to 980°C.
7. 7. The dental porcelain according to claim 1, wherein in color measurement data according to the L*a*b* color system after firing at 880° C. to 980° C., L* is 90.0 or more.
8. The main component of the crystalline component is the crystalline TiO 2 The dental porcelain according to any one of claims 1 to 7,
9. Glass components and crystalline TiO 2 The method for producing a dental porcelain according to any one of claims 1 to 8, further comprising a step of heat treating the above at 750°C to 880°C.
10. A method for producing a dental prosthesis, comprising the steps of applying the dental porcelain according to any one of claims 1 to 8 onto a zirconia substrate, and firing the dental porcelain at 880°C to 980°C.
Citation Information
Patent Citations
Crystallized glass for dental crown, and its preparation
JP1986091041A
Production of dental crown restoring material and kit used therein
JP1990045048A
Method for controlling transparency of glass ceramics
JP1995126039A
Dental opaque porcelain
JP1998094550A
Crystallized glass
JP1998182187A
